Effective debriefings in the clinical setting: a pilot study to test the impact of an evidence based debriefing app on anesthesia care providers’ performance - Seelandt, Julia C; Schneider, Jeannine; Kolbe, Michaela; Grande, Bastian (Frontiers in Medicine, 2024)
Background Debriefing enhances team learning, performance, and patient safety. Despite its benefits, it’s underused. To address this, we developed an evidence-based debriefing app. Methods This pilot study, conducted at a Swiss hospital, evaluated team performance during two anesthesia inductions using the Team Performance Scale (TPS). Following the first induction, teams engaged with the Zurich Debriefing App, with debriefing sessions meticulously recorded for subsequent evaluation. To mitigate bias, raters underwent comprehensive TPS training. The debriefings were analyzed through the DE-CODE framework. We utilized paired t-tests to examine performance improvements and linear regressions to assess the impact of reflective statements on performance, moderated by psychological safety. Results Team performance significantly improved from the first to the second induction (t (9) = −2.512, p = 0.033). Senior physicians’ (n = 8) reflective statements predicted post-assessment TPS scores (R2 = 0.732, p = 0.061), while consultants (n = 7) and nurse anesthetists (n = 10) did not. Interaction analysis revealed no moderation effects, but a main effect indicated the significance of senior physicians’ reflective statements. Conclusion This pilot study confirms the efficacy of the evidence-based debriefing app in enhancing anesthesia team performance. Senior physicians’ reflective statements positively influenced performance; however, no moderation effects were observed. The study highlights the potential of debriefing apps to streamline and enhance team debriefing processes, with significant implications for improving clinical practice and patient safety. Further research is needed to validate these findings on a larger scale and optimize the integration of debriefing into routine clinical practice.